Adaptive fixed-time consensus tracking control method for second-order multi-agent systems with disturbances. Issue 3 (February 2020) - Li, Guofei; Wu, Yunjie; Liu, Xiaocen
Abstract: The consensus tracking control problem is investigated in this paper for second-order multi-agent systems in the presence of external disturbances. A fixed-time consensus tracking control method is presented with the control parameters updated by relative information of system states. The states of multi-agent systems can track the desired signal in fixed time cooperatively. Different from most existing fixed-time control methods, the structure of proposed strategy can be changed with respect to the operation condition by the continuous transition, which facilitates the protocol design in improving both the transient and steady performance. In addition, the adaptive law with smooth function is designed to attenuate the harmful chattering. Numerical simulation is carried out to validate the effectiveness of the proposed strategy.